CURRENT STATUS OF EXTERNAL AUDIT AND FINANCIAL CONTROL IN PRESCHOOL EDUCATION SYSTEM - Safarov Aziz Mamatovich (Academia Science Repository, 2023)
The state budget is a centralized monetary fund formed in order to ensure the functions and tasks of the state in the society reflected in the constitution and laws. As long as the state exists, its functions and tasks exist, and the provision of state functions, in turn, creates an objective need for financial resources. Only in Article 41 of the Constitution of the Republic of Uzbekistan, the sentence "free general education is guaranteed by the state" and "compulsory general secondary education" obligates the state to provide 11 years of free general education in schools to all citizens. In order to ensure this function, it is necessary to build and repair, equip, and organize education for free general secondary education schools that cover all of the general education age at the expense of state funds, and provide jobs for teachers who teach in schools. it will be necessary to carry out expenses such as paying fees.